STUDI PENDAHULUAN TENTANG PERSEPSI PETANI TERHADAP MANFAAT RANCANGAN EKOSISTEM BERBASIS PENCATATAN AKTIVITAS & TRANSAKSI DIGITAL, DALAM MEMBERIKAN PELUANG PENINGKATAN PENDAPATAN PETANI. (STUDI KASUS PADA PETANI PEPAYA DI YOGYAKARTA) - Dionysius Wim Prihanto (Universitas Multimedia Nusantara, 2020)
In oder to increase farmers' income, innovation is needed in agriculture business that focuses on empowering farmers as the main actors. An agricultural ecosystem is needed that puts farmers on par with other stakeholders. So a digital agricultural ecosystem is designed, inspired by SFVCD FAO and the writer’s experience in accompanying farmers from 2015 to 2019. The design of this agricultural digital ecosystem ensures the role of digital technology so that the ecosystem can run openly, fairly and get commitment from all stakeholders in its implementation. The purpose of this preliminary study is to determine the feasibility of designing agricultural digital ecosystems by knowing farmers' perception of the 3 benefits of the design of the agricultural digital ecosystem in providing opportunities to increase farmers' income. The design of this agricultural digital ecosystem ensures the position of farmers on a par with other stakeholders, namely market providers, cultivation ordinance providers, production facilities providers, technology providers, fund providers and ecosystem guarantors. The use of digital technology to ensure that the ecosystem can run openly, fairly and get commitment from all stakeholders in its implementation. This digital ecosystem relies on recording activities and transactions digitally by farmers and other stakeholders in line with the increasing literacy of digital technology among agricultural businesses. This research uses case study approach of papaya farmers in Yogyakarta. The results of this research showed that the stakeholder of papaya farmers in Yogyakarta is only one buyer of harvest or offtaker. As for agriculture practices provider and funding does not involve other parties or made / borne by farmers themselves. The results showed that the benefits of price certainty at the beginning and certainty of procedures and means of production in the design of the digital ecosystem of agriculture are perceived by farmers as an opportunity to increase farmers' income, while the benefits of funding availability is perceived by farmers as a chance of reducing farmers' income. Farmers give input on the need for proof of success in the procedures of cultivation and production advice and make the availability of funds as an option (not mandatory) in the development of the next agricultural digital ecosystem design Keywords: Digital Agro Ecosystem, Farmers Income, Farmers Empowerment